PTH-046 Microrna expression profiling in the plasma of patients with ulcerative colitis and colitis associated cancer. (22nd June 2015) - Patel, M; Verma, AM; Aslam, I; West, K; Jameson, J; Pringle, H; Singh, B
Abstract : Introduction: Patients with Ulcerative Colitis (UC) are at risk of developing Colorectal Cancer, termed Colitis Associated Cancer (CAC) and are entered into a screening programme. However, colonoscopy based screening is resource intensive, invasive, can cause harm and can miss dysplastic (pre-malignant) lesions. Thus, novel, accurate biomarkers are appealing for surveillance purposes and to facilitate early treatment. This study aimed to investigate the potential of MicroRNA molecules to act as blood based biomarkers of disease progression and risk in the UC population. Method: Bloods samples were collected from patients with UC, prior to surveillance colonoscopy. Total RNA was isolated from samples and processed. Applied TaqMan® human miRNA array cards (Pool A and Pool B) were used to screen for the differential expression of 754 microRNAs in the discovery cohort: active UC (n = 8), chronic UC (n = 8), primary sclerosing cholangitis (n = 8), dysplasia (n = 2), CAC (n = 4). Quantitative real-time polymerase chain reaction (qPCR) was then used to validate high priority microRNA candidates in a further, independent cohort. Results: Array data was analysed using t-tests, fold changes and rank order. 28 microRNAs were chosen for further validation. Analysis of variance was used to assess differences between groups. MicroRNA 375 was shown to be significantly up-regulated in the CAC cohort (p = 0.01). Cox-regression analysis showed a Cox hazard ratio of 1.91 (p = 0.01), when based on microRNA 375 and duration of disease. Conclusion: This is the first study to investigate the expression of microRNAs in the plasma of patients with UC and CAC. The study shows the up-regulation of microRNA 375 in cases of CAC. Combining several microRNAs in a panel increased the capacity of the test to distinguish between CAC and different UC activity states. This suggests that a panel of microRNAs has potential as blood based screening test. Disclosure of interest: None Declared.